Response of rapeseed to nitrogen fertilisation in a mediterranean environment - Rodrigues, M.A. (2011)
Portugal needs urgently to increase the production of vegetable oils to be able to meet the mandatory 10% minimum target to be achieved by all member states for the share of biofuels in transport petrol and diesel consumption by 2020 (Directive 2009/28/EC). Rapeseed oils the main raw material used in Europe for the manufacture of biofuels. Portugal, however, does not produce rapeseed oil, in spite of some studies have indicated that there are favourable ecological conditions to do that around the country [I, 2].